A shape-persistent arylene ethynylene macrocycle with a multiple acetamide modified cavity: synthesis and gelation. Issue 11 (24th February 2021) - Ruan, Yang; Li, Qian-Hui; Shu, Lijin; Wan, Jun-Hua
Abstract : Strong H-bonds suppress π–π stacking leading to an AIEE gel from a planar conjugated macrocycle. Abstract : A new arylene ethynylene macrocycle (AEM) molecule bearing endo -acetamide groups was obtained by a Pd/Cu mediated homo-coupling reaction. Introducing tetraethylene glycol ether as a linkage between two C-shaped fragments substantially improved the final cyclization yield (30%). Concentration-dependent 1 HNMR experiments indicated that strong aggregates formed through H-bonds were observed for this new macrocycle with amide groups in solution. And also, this macrocycle was fluorescent in solution and showed a highly selective fluorescence quenching response toward the highly toxic Hg 2+ . More importantly, this macrocycle could induce gelation of several solvents. Significantly, an interesting aggregation-induced enhanced emission (AIEE) behavior was observed for this macrocycle upon gelation. Both SEM and TEM investigations revealed that nanoporous structures existed in the xerogels. This study offers a new molecular design approach to develop fluorescent gels from planar AEM molecules with a functional cavity.